1998
DOI: 10.1152/ajpcell.1998.275.6.c1591
|View full text |Cite
|
Sign up to set email alerts
|

Fluid shear-induced mechanical signaling in MC3T3-E1 osteoblasts requires cytoskeleton-integrin interactions

Abstract: Mechanical stimulation of bone induces new bone formation in vivo and increases the metabolic activity and gene expression of osteoblasts in culture. We investigated the role of the actin cytoskeleton and actin-membrane interactions in the transmission of mechanical signals leading to altered gene expression in cultured MC3T3-E1 osteoblasts. Application of fluid shear to osteoblasts caused reorganization of actin filaments into contractile stress fibers and involved recruitment of β1-integrins and α-actinin to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
265
5

Year Published

2000
2000
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 381 publications
(288 citation statements)
references
References 35 publications
18
265
5
Order By: Relevance
“…Yet, as shown by us and others, MC3T3-E1 cells are sensitive to fluid flow 22,40,[57][58][59] Also, we have shown that, although osteocytes are most sensitive to fluid flow, osteoblasts are sensitive to flow as well. 60 It was shown that MC3T3-E1 cells have the capacity to form calcified bone tissue in vitro and differentiate into osteoblasts and osteocytes 61 and that MC3T3-E1 cells display a time-dependent and sequential expression of osteoblast characteristics analogous to in vivo bone formation.…”
Section: Discussionsupporting
confidence: 82%
“…Yet, as shown by us and others, MC3T3-E1 cells are sensitive to fluid flow 22,40,[57][58][59] Also, we have shown that, although osteocytes are most sensitive to fluid flow, osteoblasts are sensitive to flow as well. 60 It was shown that MC3T3-E1 cells have the capacity to form calcified bone tissue in vitro and differentiate into osteoblasts and osteocytes 61 and that MC3T3-E1 cells display a time-dependent and sequential expression of osteoblast characteristics analogous to in vivo bone formation.…”
Section: Discussionsupporting
confidence: 82%
“…For example, application of strain to osteoblasts increases mRNA levels of Cox-2 (cyclooxygenase-2) and the immediate early gene c-fos within an hour [2], as well as the levels of extracellular matrix proteins osteopontin and osteocalcin within 24 hours [3]. In both proliferating and matrix-forming chondrocytes, cyclic mechanical strain can increase parathyroid-hormone-related protein mRNA levels [4].…”
Section: Introductionmentioning
confidence: 99%
“…During a routine exercise under earth's gravity, loads transmitted to diaphyseal cortical bone are dissipated at least in part through deformation of viscoelastic joint tissues. The deformation of bone is known to generate strain-induced viscous fluid flow (Piekarski et al, 1977;Tate et al, 2000), and flow-driven shear stress is considered to stimulate proliferation and differentiation of osteoblasts (Pavalko et al, 1998;Reich et al, 1990;Ryder et al, 2001) and osteocytes (Ajubi et al, 1999;KleinNulend et al, 1995). Since some part of bone deformation is generated in joints, we investigated a possibility that direct deformation of joints without any strain in cortical bone would stimulate bone formation in diaphyseal cortical bone.…”
Section: Introductionmentioning
confidence: 99%